Description of the change laboratory: A proposal for learning to learn in the school organization. - Brito Rivera, Hugo Armando (Emerging Trends in Education, 2022)
It is discussed, at a descriptive and exploratory level, how the Change Laboratory (LC) can contribute to the development of Learning to Learn (L2L) in the school organization. The relevance of developing this competence to face rapidly changing and increasingly volatile educational contexts is pointed out. Given that teaching L2L involves skills that involve different levels of collective activity, LC is proposed as a coherent model to develop this competence from an organizational perspective. The intervention is proposed as an arena for negotiation and renewal of meanings oriented to the increase of L2L from the knowledge and experimentation of its components. The aim of the paper is to answer: Which training models contribute to the reformulation of professional practices in order to promote L2L in the school? How is it possible to contribute to the conformation of a repertoire of educational practices coherent with the values and attributes of such competence? The article subscribes principles of activity theory through the notions of activity system and expansive learning, useful to approach the process of organizational learning in front of the qualitative transformation of school work.Keywords: Learning to Learn, Change Laboratory, formative intervention, activity theory, description.